2009
DOI: 10.1128/aac.00492-09
|View full text |Cite
|
Sign up to set email alerts
|

Body Weight Cutoff for Daily Dosage of Efavirenz and 60-Week Efficacy of Efavirenz-Based Regimen in Human Immunodeficiency Virus and Tuberculosis Coinfected Patients Receiving Rifampin

Abstract: Seventy-one human immunodeficiency virus-infected patients with tuberculosis who were receiving a rifampin (rifampicin)-containing regimen were initiated on treatment with efavirenz at 600 mg/day plus stavudine-lamivudine. Fasting efavirenz concentrations at 12 h after dosing (C 12 ) were monitored. The mean ؎ standard deviation efavirenz C 12 at weeks 6 and 12 and after rifampin discontinuation were 4.5 ؎ 4.3, 3.8 ؎ 3.5, and 3.5 ؎ 2.7 mg/liter, respectively. High body weight was associated with a low efaviren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 17 publications
(11 reference statements)
3
15
1
Order By: Relevance
“…Both CYP2B6 516/983 "fast metabolizers" as well as higher body weight appeared to predict a lower efavirenz concentration with rifampin therapy. The data from this controlled pharmacokinetic study support the findings of several studies demonstrating a relationship between efavirenz concentrations and body weight (24,26,39), as well as with CYP2B6 516G3T polymorphisms (8,19,20,34,40).…”
Section: Discussionsupporting
confidence: 77%
“…Both CYP2B6 516/983 "fast metabolizers" as well as higher body weight appeared to predict a lower efavirenz concentration with rifampin therapy. The data from this controlled pharmacokinetic study support the findings of several studies demonstrating a relationship between efavirenz concentrations and body weight (24,26,39), as well as with CYP2B6 516G3T polymorphisms (8,19,20,34,40).…”
Section: Discussionsupporting
confidence: 77%
“…By multivariate analyses, efavirenz concentrations persistently decreased 0.7 mg/liter (coefficients ϭ Ϫ0.07) for every 10-kg increase in patient body weight. A cross-sectional study from the Liverpool therapeutic drug monitoring registry and a study in Thais showed that body weight was an independent predictive factor for the plasma efavirenz concentration (20,21), although some previous studies were not able to demonstrate this effect (22,23). Moreover, patients' body weights increased over time while on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial interpatient variability of efavirenz concentrations with a Ͼ100% coefficient of variation after fixed standard doses is well known. Previous reports in Thais demonstrated wide ranges of interpatient variability, ranging from 77% to 136% (6,24). This can be explained by the fact that other SNPs were excluded before the final analysis, and only the patients who carried CYP2B6 haplotype *1/*1 were enrolled, suggesting that other factors that potentially influence efavirenz concentration were minimized, even if variation is usually even greater when efavirenz was coadministered with rifampin (25,26).…”
Section: Discussionmentioning
confidence: 99%